2021
DOI: 10.3389/fphar.2020.600266
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Orphan G Protein-Coupled Receptor GPR37L1 in Mice Alters Cardiovascular Homeostasis in a Sex-Specific Manner

Abstract: GPR37L1 is a family A orphan G protein-coupled receptor (GPCR) with a putative role in blood pressure regulation and cardioprotection. In mice, genetic ablation of Gpr37l1 causes sex-dependent effects; female mice lacking Gpr37l1 (GPR37L1−/−) have a modest but significant elevation in blood pressure, while male GPR37L1−/− mice are more susceptible to cardiovascular dysfunction following angiotensin II-induced hypertension. Given that this receptor is highly expressed in the brain, we hypothesize that the cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
(50 reference statements)
0
5
1
Order By: Relevance
“…An interesting observation was that Gpr37l1 −/− exhibited significantly lower ambulatory activity than wildtype controls during their active period. This was not seen in the younger chow-fed mice in this study, though a previous study in this same mouse line that measured locomotor activity by radiotelemetry reported significantly lower activity in male Gpr37l1 −/− mice at 14–15 weeks old [ 10 ]. These differences in activity between Gpr37l1 −/− mice and their wildtype controls were not associated with significant genotype effects on energy expenditure or body weight in the aged mice.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…An interesting observation was that Gpr37l1 −/− exhibited significantly lower ambulatory activity than wildtype controls during their active period. This was not seen in the younger chow-fed mice in this study, though a previous study in this same mouse line that measured locomotor activity by radiotelemetry reported significantly lower activity in male Gpr37l1 −/− mice at 14–15 weeks old [ 10 ]. These differences in activity between Gpr37l1 −/− mice and their wildtype controls were not associated with significant genotype effects on energy expenditure or body weight in the aged mice.…”
Section: Discussioncontrasting
confidence: 55%
“…The present study was designed to investigate the metabolic effects of the deletion of Gpr37l1 in mice, by thoroughly characterising the metabolic profile of Gpr37l1 −/− mice compared with wildtype ( Gpr37l1 +/+ ; C57BL/6J background) littermate controls. We have previously characterised this Gpr37l1 knockout mouse line and used it in studies investigating the cardiovascular effects of GPR37L1 [ 9 , 10 ], and this study investigates heretofore unexplored metabolic roles for this receptor. We chose to approach this question from two angles, using a high-fat diet (HFD) feeding protocol to investigate possible differences in the onset of obesity in these mice ( Figure 1 a,b), alongside a longitudinal cohort to investigate any changes in body composition over one year ( Figure 1 c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations